Complementary Molecular Dynamics and X-ray Reflectivity Study of an Imidazolium-Based Ionic Liquid at a Neutral Sapphire Interface - Brkljaca, Zlatko; Klimczak, Michael; Milicevic, Zoran; Weißer, Matthias; Taccardi, Nicola; Wasserscheid, Peter; Smith, David M.; Magerl, Andreas; Smith, Ana-Suncana (Journal of Physical Chemistry Letters, 2015)
Understanding the molecular-level behavior of ionic liquids (ILs) at IL–solid interfaces is of fundamental importance with respect to their application in, for example, electrochemical systems and electronic devices. Using a model system, consisting of an imidazolium-based IL ([C2Mim][NTf2]) in contact with a sapphire substrate, we have approached this problem using a complementary combination of high-resolution X-ray reflectivity measurements and atomistic molecular dynamics (MD) simulations. Our strategy enabled us to compare experimental and theoretically calculated reflectivities in a direct manner, thereby critically assessing the applicability of several force-field variants. On the other hand, using the best-matching MD description, we are able to describe the nature of the model IL–solid interface in appreciable detail. More specifically, we find that characteristic interactions between the surface hydroxyl groups and donor and acceptor sites on the IL constituents have a dominant role in inducing a multidimensional layering profile of the cations and anions.